2020
DOI: 10.1002/dac.4424
|View full text |Cite
|
Sign up to set email alerts
|

Semantic analysis on social networks: A survey

Abstract: Summary As social networks are getting more and more popular day by day, large numbers of users becoming constantly active social network users. In this way, there is a huge amount of data produced by users in social networks. While social networking sites and dynamic applications of these sites are actively used by people, social network analysis is also receiving an increasing interest. Moreover, semantic understanding of text, image, and video shared in a social network has been a significant topic in the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 182 publications
(322 reference statements)
0
15
0
Order By: Relevance
“…6 indicates that images and videos (54.13%) are more often shared on social networks than text information (32.33%). Video analysis carried out by Bayrakdar et al [8] found that of the variety of multimedia content that can be shared, images and videos dominate social networks. It is important to note that social networks are generally designed around cinematographic media sharing, including photography and videography.…”
Section: Methodology and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…6 indicates that images and videos (54.13%) are more often shared on social networks than text information (32.33%). Video analysis carried out by Bayrakdar et al [8] found that of the variety of multimedia content that can be shared, images and videos dominate social networks. It is important to note that social networks are generally designed around cinematographic media sharing, including photography and videography.…”
Section: Methodology and Proceduresmentioning
confidence: 99%
“…These common interests may be academic, business-oriented, professional, personal, or merely social [7]. Social networks promote individuals' social connections through virtual environments, allowing for instant communication [8]. In this study, social networks are contextually understood as collections of tools and facilities with which groups of individuals (particularly, in the context of this work, groups of schoolgoing learners) who share common interests can interact.…”
Section: The Move Onlinementioning
confidence: 99%
“…Extensive research has already surveyed and defined the hierarchical schema of SNS [8] which have been used in various research studies, for example, text mining research to explore the trending or popular actions [9]. Studies have also defined areas for potential future research [10], while others have applied semantic analysis of SNS to track and assess the influence of content shared across these platforms [11]. Whilst some of this research has touched on the physical realm associated with cyber influence, most of this prior research is limited to only the cyber realm.…”
Section: Background and Related Workmentioning
confidence: 99%
“…The exploitation of multimedia data to analyze social networks has resulted in Multimedia Social Networks (MSNs), which support new ways of user-to-user and user-to-content interaction [1,2].…”
Section: Introductionmentioning
confidence: 99%